Dairy Cattle Business Development Through Agribusiness System Supporting Business District of Karangploso Ngijo in The Village of Malang Regency - Puriastuti Hadiani, Dimas Pratidina; Susanto, W. E. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Milk as one of protein source from animal besides beef has large contributes for thenutrition fulfillment. The potential of dairy cows in Indonesia is enormous. The Ngijo village inKarangploso District of Malang Regency is one of the centers of dairy cattle. Dairy farmers are inpartnership with the cooperative to distribute the production. Most farmers in the Ngijo village inKarangploso District of Malang became a member of KUD Karangploso. The aim of this study was todetermine the role of co-operatives as the agribusiness system supporting business in thedevelopment of dairy farm in the Ngijo village. As sample are 50 farmers belonging to cooperativesin the Ngijo village. Direct observation and interviews method conducted to retrieve data directly.The results showed that the cooperative has a very important role for the business development ofthe dairy farmers in the Ngijo village. But this has not been supported by the institutional capacity ofcooperatives in improving the welfare of members of the cooperative in this respect is the dairyfarmers. Breeders still require training and counseling as a provision to increase the business interms of both quality and quantity.Key Words: Business Development, Dairy Cattle, System Agribusiness, Cooperative